Cell density and solvent are critical parameters affecting formazan evaluation in MTT assay - Gasque,Kellen Cristina da Silva (2014)
The aim of this study was to establish the more accurate protocol for fibroblast cell viability using MTT assay. NIH/3T3 fibroblasts were seeded at the following cell densities: 3.125x10³; 1.156x10(4); 3.125x10(4); 1.156x10(5) and 3.125x10(5) cells/cm². Following 24h of seeding, MTT was added to the wells. After 4h of the MTT addition, different solvents were added to solubilize the formazan crystals: 1) HCl/SDS group- 20% SDS and 0.01 M HCl; 2) EtOH/ HAc group-50% ethanol and 1% acetic acid; 3) DMSO group- 99.5% dimethyl sulfoxide; and 4) PropOH group- 99.5% isopropanol. The absorbance values were measured using a spectrophotometer at 570 nm. The data were analyzed by 2-way ANOVA (p<0.05) and showed that the absorbance average varied according to the number of cells and solvents: HCl/SDS (0 to 0.13), EtOH/HAc (0 to 0.22), DMSO (0.76 to 1.31) and PropOH (0.66 to 1.04). The DMSO and PropOH groups presented the most appropriate protocols for NIH/3T3 fibroblasts cell viability, especially at the density of 1.156x10(4) cells/cm².